RELASI MAKNA ADJEKTIVA DASAR DALAM BAHASA MADURA DI KELURAHAN KAUMAN KECAMATAN BENUA KAYONG, KETAPANG - Mashudi, Jeffry; Salem, Laurensius; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractBMDK is a language used by Madurese Ketapang people who live in Kauman Village, Benua Kayong Subdistrict, Ketapang District. A common problem in this research is the relation of meaning of basic adjective in BMDK. The general problem is subdivided into two sub-connections of the meaning of synonyms of the basic adjective and the relation of the meaning of antonyms of the basic adjective in BMDK. The method used in this research is descriptive method with the form of skin research. Based on the research results in BMDK there are synonyms and antonyms that are analyzed based on the basic adjectives. In this study there are thirteen pairs of basic adjective synonyms divided into three types of synonyms namely total and complete synonyms, total but complete synonyms and synonyms are total but not complete, whereas synonyms are not total and not complete is not found in research this. There are twenty-four basic antimony antimiments in this study that are divided into three types of antonyms, namely absolute antonyms, polar antonyms, and multiple antonyms, whereas hierarchial anonymous anonymous antonyms are not found in this study.Keyword: Relation, mean and adjective.